An Analysis of Code-Switching in The Indonesian Series ‘Kaget Nikah’ - Hilvita, Hilvita; Miftahul Jannah; Fauzan, Fauzan (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2024)
Code-switching is an exchange of two or more languages used by bilingualism or multilingualism in communicating to convey the content of the conversation easily. Nowadays, language switching is widely used among youth who master more than one language, so many trends in the millennial generation like to use language switches. Code-switching is a sociolinguistic phenomenon that occurs in bilingualism which refers to the alternation of two languages in conversation that aims to make it easier to understand the content of the conversation or for certain reasons. In this study, the writer selected two research subjects and selected all 10 episodes to be studied. This research aimed to discover what types of code-switching are found in the Indonesian series ‘Kaget Nikah’ and the types of code-switching frequently used in the series. The writer used a qualitative descriptive design with a content analysis approach. The writer descriptively analysed the phrases, sentences, English- Indonesia, and Indonesia-English words spoken by actors in the series. The instrument used to gather data is an observation sheet in the form of an observation checklist. The subjects of this study were two actors in the series. Therefore, Aurora Ribero and Kevin Julio. The results of the study showed that there were 147 code- switching data obtained, including tag switching as many as 52 (35.37%) data, inter- sentential switching as many as 32 (21.76%) data, and intra-sentential switching as many as 63 (42.85%) data. Based on these results, it can be concluded that the type that appears most often and is most dominantly used in this series is the intra- sentential switching type.